A preliminary study of the thermal strain experienced by dive support boat personnel. Issue 1 (31st December 2023) - Saunders, Samantha; Furby, Will; Chillingsworth, Kieran; Walker, Ella F; White, Graham
ABSTRACT: Anecdotal evidence indicated some British military dive support boat personnel suffer from uncomfortably cold hands and feet, which could impair their performance and be associated with reductions in core body temperature. This study collected preliminary data on thermal stress and cognitive performance of personnel taking part in a cold-weather training exercise. Six men were monitored during four boat transits in a range of climatic conditions (air temperature +1.2°C to −10.5°C, wind chill −4.5°C to 19.3°C). Core body temperature was measured with a radio pill and 12 skin sites (ISO 9886 plus hand, finger, foot and toe) with iButtons or thermistors. Self-reported thermal comfort and thermal sensation was also recorded. Reaction time and selective attention were measured pre- and post-transit. Participants' physical characteristics and personal clothing ensembles were recorded. No participant became hypothermic. Most participants' hand, foot and digit temperatures fell to below 15°C, indicating a risk of impaired dexterity, in addition to that arising from gloves. During the trial, hand and digit temperatures occasionally fell below 10°C. The limited data collected showed personal clothing choices could provide adequate thermal protection for these conditions and temperatures, and highlighted inter-individual variation and the need to allow for significant variation of day-to-day environmental conditions.